Editors' Note - Cohn, Ellen R.; Cason, Jana (International Journal of Telerehabilitation, 2016)
The Spring 2016 issue of the International Journal of Telerehabilitation (IJT) presents original and innovative work in three diverse sections: usability, intervention, and pedagogy, followed by a book review on teleaudiology. The contributors to this issue are notably multi-disciplinary and include an audiologist, computer scientists, engineers, an epidemiologist, occupational therapists, a rehabilitation counselor, a physician (physical medicine and rehabilitation), and speech-language pathologists. The common thread linking the Journal’s authors and their manuscripts, is excellence in telerehabilitation related innovation.